Information and Communication Technologies in Tourism 2023 Proceedings of the ENTER 2023 eTourism Conference, January 18-20, 2023 - Ferrer-Rosell, Berta; Massimo, David; Berezina, Katerina (Springer Proceedings in Business and Economics, 2023)
This open access book provides an extensive overview of the usage of information and communication technologies in the tourism and hospitality industry. It presents the proceedings of the International Federation for IT and Travel & Tourism (IFITT)'s 30th Annual International eTourism Conference, which assembles the latest research presented at the ENTER2023 conference. The enclosed papers cover various topics within the field, including augmented and virtual reality, website development, social media use, e-learning, big data, analytics and recommendation systems.